Racial Discrimination and Denial of Justice in Colson Whitehead’s The Nickel Boys (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims at an analysis of the novel The Nickel Boys of Colson Whitehead so as to bring out his treatment of racial abuse, physical and mental torture, deprivation of justice and education, and the isolation of the Blacks by the Whites in American society. Racism is the belief that establishes the superiority of one group of people over another. Whites assume superiority over the Blacks in America. It is deeply rooted in the American society. Even though, science and technology have developed in leaps and bounds, the ill-treatment of the coloured people by the White supremacists in American society has not stopped.  Blacks in America still face discrimination, injustice and bigotry on the basis of their colour. Colson Whitehead, the eminent African American writer highlights the ugly face of racism and the injustice done to the coloured people in The Nickel Boys. In the novel, he depicts the sad life of the Black boys in a reform school. The White wardens show their vulgarity and cruelty towards them without considering their age. The novel is based on the true story that occurred at the Dozier reform school in Florida. The protagonist, Elwood Curtis is grabbed for the crime that he has not done. He is unfairly caught up in the criminal justice system while he is travelled in a car stolen by a Black man to attend a class. The car proves to be a stolen one and Elwood Curtis has hitchhiked it. Life in the reform school worsens day by day for Elwood Curtis. Justice is denied to him and cruelty shown to him is vicious. Unfortunately, the outside world does not know about the cruelties committed against the boys in the reform school. For the parents of the Black inmates, they are getting good values and manners; the brutality is fully hidden from them. Colson Whitehead has adeptly brought out the brutalities committed by the White Superintendent Maynard Spencer, Harper and other White officials against the Black boys. Justice is denied to the Black boys and some of them are severely beaten to death at the “White House” of the prison (the reform school).  In fact, the White officials have exploited the boys in the name of reform. The deaths of the boys are turned into escapes of them. They maintain secret graveyard to bury the dead ones. The severely beaten ones are informed as sick to the parents. Colson Whitehead has depicted vividly the injustice and cruelties committed against the Blacks by the Whites in the novel.